Differential diagnoses and management strategies in patients with schizophrenia and bipolar disorder - A Carlo Altamura (Dove Medical Press, 2008)
A Carlo Altamura1, Jose M Goikolea21Department of Psychiatry, University of Milan, IRCCS Fondazione Ospedale Maggiore Policlinico Mangiagalli e Regina Elena, Milan, Italy; 2Bipolar Disorder Program, Hospital Clinic i Universitari, Barcelona, SpainAbstract: Successful treatment of psychiatric disorders, including bipolar disorder and schizophrenia, is complicated and is affected by a broad range of factors associated with the diagnosis, choice of treatment and social factors. In these patients, treatment management must focus on accurate and early diagnosis, to ensure that correct treatment is administered as soon as possible. In both disorders, the treatment of the disease in the acute phase must be maintained long term to provide continuous relief and normal function; the treatment choice in the early stages of the disease may impact on long-term outcomes. In schizophrenia, treatment non-compliance is an important issue, with up to 50% of patients discontinuing treatment for reasons as diverse as efficacy failure, social barriers, and more commonly, adverse events. Treatment non-compliance also remains an issue in bipolar disorder, as tolerability of mood stabilizers, especially lithium, is not always good, and combination treatments are frequent. In order to achieve an optimal outcome in which the patient continues with their medication lifelong, treatment should be tailored to each individual, taking into account treatment and family history, and balancing efficacy with tolerability to maximize patient benefit and minimize the risk of discontinuation. These case studies illustrate how treatment should be monitored, tailored and often changed over time to meet these needs.Keywords: bipolar disorder, recurrence, treatment management, schizophrenia, non-compliance, adverse events